Fertility Lifetables of Glasshouse Whitefly Trialeurodes vaporariorum (Westwood) on French Bean cv. Contender at Different Temperatures - Kapil, Jyoti; Tomar, Manica (International Journal of Economic Plants, 2020)
Fertility Life tables and characteristics of the Trialeurodes vaporariorum (Westwood) were assessed on French bean cv. Contender at different temperatures 15, 20, 25 and 30 °C. The life table analysis showed that the females lived for a maximum of 58 days at 15 °C. The trend of oviposition showed a peak on 32nd day at 25 °C as the highest number of eggs produced per female per day was 9.98. The true Intrinsic rate of increase (rm) values were 0.123 and 0.121 at 20 °C and 25 °C, respectively. The rate of natural increase (rc) was 0.120 at 20 °C and 25 °C. The highest net reproductive rate (45.86) was obtained at 20 °C. The population doubling time (DT) was maximum (10.42 days) at 15 °C and minimum (5.64 days) at 20 °C. Generation time was 47.17 days at 15 °C which decreased to 24.82 days at 30 °C.